An Introduction to Ontology Engineering - Keet, Maria; Open Textbook Library (Open Textbook Library, 2018)
This first general textbook An introduction to ontology engineering has as main aim to provide the reader with a comprehensive introductory overview of ontology engineering. A secondary aim is to provide hands-on experience in ontology development that illustrate the theory. The book is divided into three blocks: Block I: logic foundations for ontologies both regarding the languages (mainly First Order predicate Logic, Description Logics, and OWL) and automated reasoning. Block II: developing good ontologies with methods and methodologies, the top-down approach with foundational ontologies, and the bottom-up approach to extract as much useful content as possible from legacy material. Block III: advanced topics with a selection of areas of specialisation, including Ontology-Based Data Access, the interaction between ontologies and natural languages (multilingual ontologies, controlled natural language), and advanced modelling with additional language features (fuzzy and temporal ontologies).
1 Introduction -- 2 First order logic and automated reasoning in a nutshell -- 3 Description Logics -- 4 The Web Ontology Language OWL 2 -- 5 Methods and Methodologies -- 6 Top-down Ontology Development -- 7 Bottom-up Ontology Development -- 8 Ontology-Based Data Access -- 9 Ontologies and natural languages -- 10 Advanced Modelling with Additional Languages Features
In English.
Description based on online resource
Keywords: Philosophy -- Textbooks